Atmospheric correction algorithms for satellite water quality surveillance - Hope, V. S.; Hadjimitsis, Diofantos G.; Clayton, C.R.I. (My University, 1997)
Atmospheric correction algorithms for satellite water quality surveillance - ePrints Soton The University of Southampton Courses University life Research Business Global About Visit Alumni Departments News Events Contact × Search the Site Search Filter your search: All Courses Projects Staff University of Southampton Institutional Repository Search Advanced Search Policies & Help Latest Download Statistics Browse by Year Browse by Divisions LeftRight Atmospheric correction algorithms for satellite water quality surveillance Hope, VS, Hadjimitsis, DG and Clayton, CRI (1997) Atmospheric correction algorithms for satellite water quality surveillance. In Observations and Interactions: Proceedings of the 23rd Annual Conference of Remote Sensing Society, Reading. Remote Sensing Society. pp. 268-273 . Record type: Conference or Workshop Item (Paper) This record has no associated files available for download…
Keywords: Algorithms; Water quality